Detecção das toxinas a/b e avaliação dos tipos toxigênicosde clostridium difficile a partir de fezes de leitões e cães - Rodrigo Otavio Silveira Silva (2011)
Clostridium difficile is a Gram-positive anaerobe responsible for cases of pseudomembranous colitis in humans. In veterinary medicine, this organism has been incriminated as the main agent of neonatal colitis in piglets, while recent reports suggest it as responsible for chronicdiarrhea and nosocomial infection in dogs. The diagnosis of infections caused by this microorganism is based on the detection of toxins A and B, while the isolation followed by genotyping of C. difficile can provide information about the epidemiology of this disease and canalso predict the potential virulence of the isolated strains. Despite the increasing importance of this agent in veterinary medicine, there are no studies about evaluated this agent in pigs and dogs in Brazil. The objective of this study was to detect toxins A and B and isolate and genotype C. difficile from stool samples of pigs and dogs. Sixty stool samples of piglets, 30 from apparently healthy and 30 from diarrheic animals, and 57 fecal samples from dogs, 35 from apparently healthy animals and 22 from diarrheic dogs. For detection of toxins A and B, acommercial ELISA kit were used according to manufacturer recomendations. For isolation of C. difficile, stool samples were plaqued on CCFA agar after alcohol-shock. Suggestive colonies were subjected to thermal extraction of DNA and the supernatant was used for PCRtemplate. Toxins A and B of C. difficile in were found in 21 (36.8%) samples from dogs, 16 (28,1%) from diarrheic and five (8.8%) from non-diarrhoeic animals. In piglets, the toxins were found in ten (16.7%) samples, seven (11.7%) from diarrheic and three (5%) from apparentlyhealthy piglets. C. difficile was isolated from 12 of 60 (20%) from pigs. Three strains were nontoxigenic (A-B-) and nine were toxigenic and, of these, four were A+B+ and five strains were AB+. Six strains (50%) isolated from pigs were positive for binary toxin (CDT+). In dogs, the agent was isolated from 12 (21%) samples, which ten strains were A+B+ and two were nontoxigenic. No variant strain was isolated from dogs. The gene responsible for encoding the binary toxin was found in only one strain isolated from this specie. It came from a non-diarrheic animal and was classified as A+B+. All non-toxigenic strains obtained in this study were isolated from apparently healthy animals. The multiplex PCR was useful for confirming the identity and to provide genotyping of C. difficile strains. In this study, a large proportion of CDT+ strains reinforce the need for more studies to evaluate the importance of binary toxin in infections caused by C. difficile in piglets. In both species, many apparently healthy animals were positive for the presence of toxins, calling attention to the possibility of the occurrence of subclinicaldisease.